Finnish education brands as country image promoters: Multiple case study of Finnish education brands in Asian and Latin American markets - Kassari, Tuuli (My University, 2016)
Building competitive country image has become increasingly important for countries. Due to globalization, a private sector has a significant role in promoting country image abroad. Brands are dominant channels of communication and they can reach high visibility. Therefore, earlier studies have suggested that brands can be more powerful in promoting country image than any governmental campaign. Finland is a quite unknown country abroad. It has successful brands but they have no relevant influence on country image. Education is becoming one of the leading export products of Finland and it is a one of the key attributes of the target country image. Therefore, the purpose of the study is to find out how Finnish country image can be promoted by education sector. The topic is approached by considering the country-of-origin (COO) effect as a two-way relation. The first part of the literature review defines the inverse COO as well as the influential factors that promote image transfer from a brand to its origin country. The second part focuses on the role of education sector in the target image of Finland. These topics form a theoretical framework, which is applied to the empirical research. The empirical research combines both qualitative and quantitative methods. The data is collected though semi-structured interviews from three Finnish education brands and though online questionnaire from 21 potential end-users in Latin America and Asia. The main findings of the study suggest that Finnish education brands have potential to influence positively on the country image of Finland. The companies should convey its provenance through its branding strategy, which should be coherent with the Finnish target image as well as support and strengthen the desired associations of the COO. In addition, in order to have an impact on the COO, the brands should differentiate themselves from other education brands, be visible in the international market and cooperate with the public sector.
Keywords: Education Export; Inverse Country-of-Origin Effect; Brand Image; Country Image; Image Transfer; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|